2005
DOI: 10.1124/jpet.105.094201
|View full text |Cite
|
Sign up to set email alerts
|

Repression of Cytochrome P450 Activity in Human Hepatocytes in Vitro by a Novel Hepatotrophic Factor, Augmenter of Liver Regeneration

Abstract: Pathological disorders of the liver were shown to be associated with an impairment of hepatic drug metabolism mediated in part by growth factors. Augmenter of liver regeneration (ALR) is a novel liver-specific hepatotrophic growth factor, whereas its action on cytochrome P450 (P450) metabolism is completely unknown. Application of ALR to primary human hepatocytes in vitro reduced P450 isoenzyme activities (1A2 and 2A6) in a dose-dependent manner. Time-course analysis revealed that the maximal inhibitory effect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 42 publications
0
23
0
1
Order By: Relevance
“…Recently, we reported that ALR induced c-myc expression and activated polyamine metabolism with both being critically important in cellular growth (17). Furthermore this isoform modulated hepatic detoxification by cross-linking growth signals to the regulation of hepatic metabolism (18). The proliferation augmenting effect of ALR was attributed to its ability to activate EGF receptor phosphorylation and the subsequent stimulation of the MAPK cascade (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we reported that ALR induced c-myc expression and activated polyamine metabolism with both being critically important in cellular growth (17). Furthermore this isoform modulated hepatic detoxification by cross-linking growth signals to the regulation of hepatic metabolism (18). The proliferation augmenting effect of ALR was attributed to its ability to activate EGF receptor phosphorylation and the subsequent stimulation of the MAPK cascade (29).…”
Section: Discussionmentioning
confidence: 99%
“…The short form of ALR (15 kDa) is found not only at extracellular sites but also at nuclear and cytosolic localizations participating in intracellular redox-dependent signaling pathways (15,16). ALR is a hepatotrophic factor stimulating proliferation of hepatocytes (17,18) and augmenting liver regeneration (15,16), thereby exerting beneficial effects in models of hepatic failure (19) and liver fibrosis (20).…”
Section: Introductionmentioning
confidence: 99%
“…Primary human hepatocytes were isolated by a modified two-step EGTA/collagenase perfusion procedure as described previously (19,20) and infected with HepAD38-derived supernatant as described previously (21). Primary mouse hepatocytes were isolated from Nrf2 Ϫ/Ϫ (22) and WT C57BL/6 mice using a two-step collagenase perfusion and cultivated as described previously (23).…”
Section: Methodsmentioning
confidence: 99%
“…Experimental procedures were performed according to the guidelines of the charitable state-controlled foundation, Human Tissue and Cell Research (HTCR), with informed patient's consent (12) and approved by the local ethics committee of the University of Regensburg. Human hepatocytes were isolated using a modified two-step EGTA/ collagenase perfusion procedure and maintained in culture as described (13,14). Viability of isolated hepatocytes was determined by trypan blue exclusion, and cells with viability >85% were used for cell culture.…”
Section: Hepatocyte Preparation and Culturementioning
confidence: 99%